Քաղաքական գովազդի առանձնահատկությունները՝ ընտրազանգվածի ուշադրությունը հրավիրելու համատեքստում - Աստղիկ Ավետիսյան; Հարություն Ծատրյան (ՀՀ ԳԱԱ հրատ.)
Политическая реклама имеет уникальное и важное место в инструментах политических технологий. Она уже давно является неотъемлемой частью предвыборных и поствыборных процессов демократических стран. Она четко сформирована, используется активно и очень уместно. В последние годы политическая реклама была значительно модернизирована: появились многочисленные а, инновационные особенности. Любая рекламная кампания в значительной степени нацелена на создание определенного образа: формирование красивой упаковки с рядом особенностей, присущих набору политических технологий. Political advertising has a unique and important place in the tools of political technology. It has long been an integral part of the pre-electoral and post-electoral processes of democratic countries. It has been clearly shaped using actively and very relevantly. In recent years, political advertising has been significantly modernized: numerous innovative peculiarities have emerged . Any advertising campaign is, to a great extent, targeted to create a certain image, in other words to make beautiful packaging and branding, which is distinguished by a number of patterns and peculiarities inherent in the political technology toolkit.
Keywords: Social Sciences; Advertising; Political Science